Post-endoscopy Barrett’s neoplasia after a negative index endoscopy: a systematic review and proposal for definitions and performance measures in endoscopy - Desai, Madhav; Lieberman, David; Srinivasan, Sachin; Nutalapati, Venkat; Challa, Abhishek; Kalgotra, Pankush; Sundaram, Suneha; Repici, Alessandro; Hassan, Cesare; Kaminski, Michal F.; Sharma, Prateek (Endoscopy, 2022)
Background A high rate of neoplasia, both high grade dysplasia (HGD) and esophageal adenocarcinoma (EAC) has been reported in Barrett’s esophagus at index endoscopy, but precise rates of post-endoscopy Barrett’s neoplasia (PEBN) are unknown.Methods A systematic review and meta-analysis was performed examining electronic databases (inception to October 2021) for studies reporting PEBN. Consistent with the definitions of post-colonoscopy colorectal cancer proposed by the World Endoscopy Organization, we defined neoplasia (HGD/EAC) detected at index endoscopy and/or within 6 months of a negative index endoscopy as “prevalent” neoplasia, that detected after 6 months of a negative index endoscopy and prior to next surveillance interval (i. e. 3 years) as PEBN or “interval” neoplasia, and that detected after 36 months from a negative index endoscopy as “incident” neoplasia. The pooled incidence rates and proportions relative to total neoplasia were analyzed.Results 11 studies (n = 59 795; 61 % men; mean [SD] age 62.3 [3.3] years) met the inclusion criteria. The pooled incidence rates were: prevalent neoplasia 4.5 % (95 %CI 2.2 %–8.9 %) at baseline and an additional 0.3 % (0.1 %–0.7 %) within the first 6 months, PEBN 0.52 % (0.46 %–0.58 %), and incident neoplasia 1.4 % (0.9 %–2.1 %). At 3 years from the index endoscopy, PEBN accounted for 3 % of total Barrett’s neoplasia, while prevalent neoplasia accounted for 97 %.Conclusion Neoplasia detected at or within 6 months of index endoscopy accounts for most cases of Barrett’s neoplasia (> 90 %). PEBN accounts for ~3 % of cases and can be used for validation in future. This highlights the importance of a high quality index endoscopy in Barrett’s esophagus and the need to establish quality benchmarks to measure endoscopists’ performance.